Evaluación técnico-financiera para la selección de la mejor alternativa de completamiento hueco abierto para un pozo nuevo en un campo ubicado en la cuenca de los Llanos Orientales (2019)
The present work allowed the evaluation of three designs of open hole completions to select the best alternative for a new well in a field located in the Basin of the Eastern Plains, by means of simulations and an economic analysis. In the first place, the generalities of the field under study were described; a theoretical framework was made describing the two main approaches of this work, the formation damage, the completion of wells and the types of completion. This work also describes theoretically the technologies implemented in the proposed open hole completion designs. After this, three representative wells for this study are chosen, detailing their mechanical states, production history, the current completion of each well, as well as their petrophysical properties. Additionally, three open hole completion designs are presented proposed by the authors, with their respective technical descriptions. Subsequently, the Spot module, the conventional completion and the open hollow completion were simulated with Prosper Nodal Analysis Software. Once the results of these simulations were obtained, a sensitivity analysis is carried out to determine the formation damage associated with the productivity of each well. Finally, a selection matrix based on technical and financial aspects of the proposed completions was carried out, which, together with a financial analysis through the Net Present Value indicator, allowed to establish the best completion option for the new well under study.